DIGITAL PORTFOLIO AS AN ASSESSMENT TOOL FOR ACADEMIC WRITING AND METACOGNITIVE DEVELOPMENT: A CASE STUDY OF STUDENT AND LECTURER PERCEPTIONS, EVIDENCED OUTCOMES, AND IMPLEMENTATION CHALLENGES IN AN INDONESIAN UNIVERSITY - Juliari, I Gusti Ayu Indah Triana; Suhardiana, I Putu Andre; Wijayanti, Astuti (UHN IGB Sugriwa Denpasar, 2025)
The gap in student-centered assessments in practice in English Language Teaching (ELT) poses a challenge in the application of 21st-century skills and Indonesia’s Merdeka Belajar-Kampus Merdeka (Freedom to Learn-Independent Campus) policy, which emphasize innovation and student-centeredness. The practice of ELT, however, continues to be product-oriented and lacks the development of metacognition. Although the development of digital portfolios is considered a resource promising, research in the Indonesian ELT context examining the micro-level implementation and influences of digital portfolios is limited. This study investigated the implementation of a digital portfolio in an Indonesian university’s English Education Department. It aimed to analyze: 1) student and lecturer perceptions of its role in academic writing and metacognitive awareness; 2) evidence of metacognitive development (planning, monitoring, evaluating) in portfolio artifacts; and 3) the challenges in its execution as an assessment tool. A qualitative single-case study design was employed. Data were collected over one semester through semi-structured interviews with 16 students and one lecturer, non-participant observation, and document analysis of the students’ digital portfolios (Padlet), which were assessed using a reflective writing rubric. The portfolios showed contradictory results that they provided opportunities for some students to exert control and experience advancement, whereas, for others, they provided too much of a cognitive load due to the lack of clarity within reflection tasks and the technical difficulties involved. Cognitive overload and technical difficulties along with unclear reflection tasks overshadowed the self-assessment opportunities in the portfolios. The challenges involved a lack of lecturer recognition regarding the potential for unsustainable workloads, the digital gap, inflexible academic calendars, and the subjectivity of assessing a learner’s metacognition. The catalyst emerged through the lecturer’s strategic sequencing which clarified the purpose of the portfolio thereby operationalizing self-regulated learning within the framework of problem-oriented learning.